Unités Paysagères et services écosystémiques, l’exemple des récifs coralliens - Gilbert David; Émilie Mirault; Gwenaëlle Pennober; Christophe Révillion (VertigO, 2012)
Ecosystem services are a recent way of thinking the world through the prism of economics. They drive to a better integration of the environment into economic and development decision making. They are subject to increasing demand, including the coral reef ecosystem management. For valuing coral reef ecosystem services, the more common way is to go through the total economic value. This total value is applied to the whole coral reef capital considered as a black box, regardless of its heterogeneity in terms of geomorphology, habitats, biotic communities and uses. This functional isotropy of this natural capital is a big constraint for integrating the valuation of ecosystem services into the local governance. The solution needs a cross cutting point of view, mixing economics and geography. Thus the reef is not only a natural capital but also a landscape composed of associated resources spaces generating specific ecosystem services. But the finance orientated trend for valuing the environment makes more and more weak this cross cutting view and drives to a deadlock. A better economic valuation of the coral reef ecosystem services needs to bridge urgently the functional ecosystem and its value. Linking the landscape and the ecosystem services could be the first step of this process.